Impact of maternal organic food consumption and diet quality during pregnancy on offspring’s risk of inflammatory bowel disease: findings from a Danish National Birth Cohort Study - Anneberg, Olivia Mariella; Olsen, Sjurdur Frodi; Hansen, Anne Vinkel; Bjerregaard, Anne Ahrendt; Halldorsson, Thorhallur Ingi; Jess, Tine; Brusco De Freitas, Maiara (Frontiers in Nutrition, 2025)
BackgroundThis study explores associations of maternal organic food consumption and diet quality during pregnancy with pediatric-onset inflammatory bowel disease (IBD) risk in offspring, including Crohn’s disease (CD) and ulcerative colitis (UC).MethodsPregnant mothers and their offspring were enrolled in the Danish National Birth Cohort, a nationwide prospective cohort study, in 1996–2002. In gestational week 30, telephone interviews assessed overall maternal organic food consumption during pregnancy. In gestational week 25, a food frequency questionnaire assessed maternal diet during the previous 4 weeks, including six different organic food types (eggs, dairy, meat, fruit, vegetables, and cereals). A Healthy Eating Index evaluated maternal diet quality based on adherence to Danish official dietary guidelines. Offspring with pediatric-onset IBD (≤18 years) were identified in national patient registries. Cox regression explored associations of maternal organic food consumption and diet quality during pregnancy with offspring’s risk of pediatric-onset IBD, CD, and UC.ResultsThe study included 60,274 singleton mother–child pairs, of which 168 children developed pediatric-onset IBD. Frequent maternal organic food consumption during pregnancy was not significantly associated with offspring’s IBD risk (HR: 0.63; 95% CI: 0.33–1.19). However, frequent organic food consumption during pregnancy, particularly organic eggs and dairy, lowered offspring’s risk of CD (HR: 0.40; 95% CI: 0.17–0.94), but not UC (HR: 1.11; 95% CI: 0.41–3.00). Maternal diet quality during pregnancy was not significantly associated with offspring’s risk of IBD (HR: 0.99; 95% CI: 0.97–1.01), CD, and UC.ConclusionIn this large prospective cohort study, we show that maternal organic food consumption, particularly eggs and dairy, during pregnancy may lower offspring’s risk of pediatric-onset CD, but not UC.